Pancasila and Islamic Religious Education as Value Sources: Regulating Civil Law and Private Justice through Islamic Sociological Jurisprudence Theory - Ahmad Muhamad Musain Nasoha; Zahrah Dwi Pusparini; Annajmul Muniiroh; Annuriyah Nabila; Awalia Rindu Az Zahra (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
This research examines how Pancasila and Islamic Religious Education function as foundational value systems in shaping civil law relations and promoting private justice, analyzed through the lens of Islamic Sociological Jurisprudence. Within Indonesia’s pluralistic yet religious societal framework, civil law extends beyond formal legal provisions and reflects the living moral, social, and religious norms embedded in the community. This study adopts a normative juridical method, complemented by conceptual and sociological approaches, and is supported by an extensive review of legal literature and scholarly discourse. The study reveals that Pancasila encapsulates essential principles, including justice, human dignity, and social equilibrium, which resonate with the ethical foundations of Islamic teachings. At the same time, Islamic Religious Education contributes significantly to cultivating legal consciousness and moral responsibility among individuals, thereby encouraging a model of private justice that transcends rigid legal formalism and emphasizes societal welfare (maslahah). From the standpoint of Islamic Sociological Jurisprudence, civil law should operate as a dynamic instrument that adapts to social realities while incorporating prevailing Islamic values. In conclusion, embedding the values of Pancasila and Islamic Religious Education within civil law frameworks enhances both the legitimacy and the substantive quality of justice. This research offers a conceptual contribution toward developing a civil law system that is more responsive, equitable, and aligned with Indonesia’s socio-cultural and religious context.